DETERMINANTS AND ASSOCIATED FACTORS AFFECTING BODY MASS INDEX AMONG STUDENTS OF UNIVERSITY AT THAILAND - Sangthong, Nattawan; Saingthong, Phromphon; Rathore, Aneeta; Dropati, FNU; Ethisan, Plernta; Ethisan, Plernta (Journal of Ayub Medical College Abbottabad, 2024)
Background: There is substantial number of youth's population belong to age group 18-25 years contributes 11% of the total population in Thailand. According to the ASEAN Youth Development Index (AYDI) ranking, Thailand is ranked 8th out of 10 countries in terms of improvement in health and well-being and social participation of youth in the country. Body mass index includes an appropriate weight and height for adult population, that is important indicator for healthy young subjects. The objectives of this study were to assess the prevalence of Body Mass Index (BMI) and affected factors among the university students. Methods: This study was conducted on the sample of 300 students by multiple stage random sampling technique. A pretested and piloted questionnaire were used in this study. Factors affected BMI were analyzed by using Multiple Linear Regression (MLR). A written consent was taken prior to conduct the data collection. Results: The variables that affected the student's BMI were Socio-demographic factors such as; gender and Body Mass Index of the mothers and health behavioural factors, including physical activity variables had a statistically significant effect on the student's BMI (p<0.001), which could explain 91.10 % of the variation in BMI. The mean of BMI was 21.50±4.655 SD. Lower than half of students (47%) had the normal BMI. However, the BMI of overweight /obese students was up to 26.67%. Conclusion: Study concluded that the factors like; gender, maternal BMI, physical activity were significantly effects on the BMI of university students in Thailand.